Ludzkie pragnienia, trudy i obawy w oświeceniowych modlitwach poetyckich - Marcinkowska, Małgorzata (Tematy i Konteksty, 2014)
The paper is devoted to poetic prayer songs of the Enlightenment, which contain references to the work and the wider circle of relationships as well as values and feelings of the individual. The considerations are focused on the analysis undertaken by the authors who concentrate on the social changes taking place in the late eighteenth century. The basic research tasks include, among other things, describing the role of poetic prayers in complex human relationships in the context of communication theory as well as genre characteristics. The main aim of the paper is to introduce the meaning and the understanding of prayer as an important part of human life that is placed in the contemporary everyday social rhythm.